Philosophical Analysis of Sustainable Development Goals - Mixon, Deborah (International Journal of Philosophy, 2024)
Purpose: The general objective of the study was to examine philosophical analysis of Sustainable Development Goals. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to philosophical analysis of Sustainable Development Goals. Preliminary empirical review revealed the crucial interplay of ethical, epistemological, and metaphysical considerations in achieving global sustainability. It highlighted the SDGs' foundation on principles of equity, justice, and human rights, emphasizing the need for inclusive and context-sensitive knowledge systems. The analysis also prompted a rethinking of traditional development notions, advocating for a holistic view that includes social and environmental well-being. The conclusion stressed the importance of integrating these philosophical dimensions into policymaking to create effective, inclusive strategies for sustainable global progress. Unique Contribution to Theory, Practice and Policy: The Utilitarianism, Deontological Ethics and the Social Contract Theory may be used to anchor future studies on the philosophical analysis of SDGs. The study recommended integrating diverse ethical perspectives into development theories, emphasizing inclusive and participatory approaches in practice, and promoting integrated policy frameworks that align with the holistic nature of the SDGs. It highlighted the need for robust monitoring and evaluation mechanisms, enhanced global cooperation, and the incorporation of sustainability and ethical considerations into educational curricula. These recommendations aimed to ensure that development efforts were economically viable, socially just, and environmentally sustainable, ultimately fostering a more inclusive and effective pursuit of the SDGs.